An Examination of Factors Associated With Self-Efficacy for Food Choice and Healthy Eating among Low-Income Adolescents in Three U.S. States - Muturi, Nancy W.; Kidd, Tandalayo; Khan, Tazrin; Kattelmann, Kendra; Zies, Susan; Lindshield, Erika; Adhikari, Koushik (My University, 2016)
Background: Self-efficacy is a crucial component in effective health communication and health promotion interventions and serves as a moderator for behavior change. Although awareness and risk perception are important in the behavior change process, self-efficacy gives people the necessary confidence in their ability to engage in advocated health behaviors. In addressing childhood obesity, self-efficacy plays a crucial role in dietary decisions. Informed by the social cognitive theory, this study examines the personal and environmental factors that determine self-efficacy for healthy food choices and healthy eating among adolescents in low-income communities.
Citation: Muturi NW, Kidd T, Khan T, Kattelmann K, Zies S, Lindshield E and Adhikari K (2016) An Examination of Factors Associated With Self-Efficacy for Food Choice and Healthy Eating among Low-Income Adolescents in Three U.S. States. Front. Commun. 1:6. doi: 10.3389/fcomm.2016.00006
Keywords: Adolescence; Ethnic Minorities; Low-Income; Obesity; Self-Efficacy; School-Based Program